Analysis of the financial situation of selected respect index companies - Joanna Stawska; Lena Grzesiak (e-Finanse: Financial Internet Quarterly, 2018)
The concept of Corporate Social Responsibility (CSR) has become popular among organizations, the public, and external stakeholders. Recently, it has been appreciated by capital markets the indexes of which are constructed in such a way as to account for companies' CSR. One of these indexes is the Respect Index of the Warsaw Stock Exchange. This paper analyses the financial condition of Respect Index companies in Poland using the desk research method. The analysis utilizes indicators of the so-called Du Pont's pyramid (for all companies under consideration) and stock market indices such as a book value per share (BVPS) and a price-to-earnings ratio (P/E) (for the banking and insurance sectors and all other sectors, respectively). The analysis shows that the financial condition of the studied Respect Index companies in the years 2013 - 2015 was stable in the period of analysis, despite the not-so-optimistic financial situation of their industries. Socially responsible management can often result in good financial position and increase in the company's rate, which may be indicated by the fact that the Respect Index increased by 40% in 2009-2015 compared to a lower increase WIG (18%) or WIG20 (-20%) decline.
Keywords: M14; N20; O12; 330; Respect Index; Corporate Social Responsibility (CSR); financial analysis